EXAMINING THE INFLUENCE OF AUDIO-VISUAL MATERIALS ON CHEMISTRY STUDENTS’ INTEREST IN LEARNING CHEMISTRY IN AWKA EDUCATION ZONE, ANAMBRA STATE, NIGERIA (UNIZIK Journal of STM Education, 2023)
The study sought to examine the influence of audio-visual materials on students' interest in learning chemistry among secondary school students in Awka Education Zone of Anambra state. Four research questions were raised to guide the study. A descriptive survey design was employed. One hundred and twenty four (124) chemistry students drawn from 1,821 senior secondary year two students (SS2) in Awka Education zone in Anambra State formed the sample for the study. Thirty (34) item structured questionnaires on a four-point rating scale developed by the researchers were used for data collection. The instrument used for data collection was questionnaire which was validated by three experts. A reliability coefficient of 0.83 was established using Cronbach Alpha techniques. After the administration of the instrument to the respondents, the data obtained were analyzed using mean, standard deviation, frequency and percentage. The finding among others revealed that some audio-visual materials are available in the chemistry classroom and they are effective in enhancing students’ interest in learning chemistry. There are factors that hinder the effective use of audio-visual materials in learning chemistry; they are lack of qualified chemistry teachers with adequate knowledge of modern audio-visual materials. It was recommended among others that government should endeavor to make adequate provision of modern audio-visual materials in schools, teachers should be 8retrained through seminars, workshops and conferences so as to enable them have adequate knowledge of the use of modern audio-visual materials.
Keywords: Audio-Visual Materials; Interest; Learning; Chemistry